Studi Kritis Terhadap Dasar Pertimbangan Hakim dalam Menjatuhkan Putusan Tindak Pidana Perjudian - Saldi Saldi; Muhammad Natsir; Suardi Suardi; Elvi Susanti Syam; Herul Herul; Firmansyah Hibbu (Jurnal Litigasi Amsir, 2025)
This study aims to analyze the judge's considerations and the application of the law in the decision of the gambling crime case at the Parepare District Court No. 20/Pid.B/2023/Pn Pre. Using normative and empirical legal research methods, this study found that the judge considered the testimony of witnesses, defendants, indictments and prosecutors' demands, as well as evidence, so that the elements of Article 303 of the Criminal Code were declared fulfilled. The defendants were legally and convincingly proven to have committed the crime of gambling. The judge also granted leniency due to mitigating circumstances, namely two elderly defendants.